Self interaction of gluons within the M.I.T. bag model - Quick, Jonathan Francis Hare (My University, 1990)
One consequence of the non-abelian nature of Quantum Chromodynamic ( QCD ) gauge theory is that its gauge particles, or gluons as they are called, must be able to interact with each other. It has long been suggested that this must give rise to a complicated QCD vacuum structure, and many attempts to describe and model such a. problem can be found in the literature. Another consequence of the self-interaction or "be gluons is the effect of colour confinement, which specifies that. only colour-charge neutral objects may exist in, free space. One of the most successful models in QCD so far takes into account this confinement effect directly, by means of a phenomenological confining potential or bag. The aim of this thesis is to consider the structure ot the QCD vacuum within the confines of such a bag. (Abbreviation abstract)
A Thesis Submitted to the Faculty of Science, University of the Witwatersrand, Johannesburg, in Fulfillment of the Requirements for the Degree of Doctor of Philosophy.
Keywords: Quantum theory; Quantum chromodynamics; Gauge fields (Physics); Gluons.